The Europeanisation of Social Protection - Sarfati, Hedva (Relations industrielles / Industrial Relations, 2009)
The Europeanisation of Social Protection, edited by Jon Kvist and Juho Saari, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; EU membership; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social policy